Proteome Analysis for Understanding Abiotic Stress (Salinity and Drought) Tolerance in Date Palm (Phoenix dactylifera L.) - Haddad A. El Rabey; Abdulrahman L. Al-Malki; Khalid O. Abulnaja; Wolfgang Rohde (International Journal of Genomics)
This study was carried out to study the proteome of date palm under salinity and drought stress conditions to possibly identify proteins involved in stress tolerance. For this purpose, three-month-old seedlings of date palm cultivar “Sagie” were subjected to drought (27.5 g/L polyethylene glycol 6000) and salinity stress conditions (16 g/L NaCl) for one month. DIGE analysis of protein extracts identified 47 differentially expressed proteins in leaves of salt- and drought-treated palm seedlings. Mass spectrometric analysis identified 12 proteins; three out of them were significantly changed under both salt and drought stress, while the other nine were significantly changed only in salt-stressed plants. The levels of ATP synthase alpha and beta subunits, an unknown protein and some of RubisCO fragments were significantly changed under both salt and drought stress conditions. Changes in abundance of superoxide dismutase, chlorophyll A-B binding protein, light-harvesting complex1 protein Lhca1, RubisCO activase, phosphoglycerate kinase, chloroplast light-harvesting chlorophyll a/b-binding protein, phosphoribulokinase, transketolase, RubisCO, and some of RubisCO fragments were significant only for salt stress.